TEORIA I PRAKTYKA OCHRONY INFORMACJI NIEJAWNYCH – WYBRANE ZAGADNIENIA DOTYCZĄCE BEZPIECZEŃSTWA INFORMACJI - Zapart, Robert (Polityka i Społeczeństwo, 2020)
A key issue for every state is the protection of information about its resources that should not be made public for various reasons, including national security reasons in particular. The article discusses the problem of its lawful protection against unauthorised disclosure in relation to emergency situations. The author claims that the discrepancies in this area result from both the provisions of the Act on the Protection of Classified Information, which allows for excessive arbitrariness, and the shortages caused by the actions of persons working in the public administration sector. A slight amendment to the current legislation, combined with training on the marking of materials that require actual protection, may ensure the systemic enhancement of the protection of classified information and thus, national security, without excessively limiting the transparency of public life.